Strand 4: Videoconferencing for Deaf People A Case Study of On-line Education for Deaf People Using Videoconferencing - Sutherland, Allan; Padden, Tessa (Proceedings of the International Conference on Networked Learning, 1998)
This paper is a case study of a BT funded project exploring and developing the use of videoconferencing for the education of Deaf adults. It is a result of staff development work within this FE College on the uses of ILT for teaching and learning. Deaf people have worked at the heart of the project which has given the work a special relevance to their needs. Deaf education has too often denied Deaf people the opportunity to influence or use their first language for reaching and learning. A series of pilot teaching sessions have been undertaken and evaluated. A great deal has been learned about the technological, pedagogical and access issues surrounding this work. It is hoped that this provision can now be developed to provide specialist courses for Deaf people taught by Deaf people.